Wewenang Dewan Perwakilan Daerah dalam Memperkuat Otonomi Daerah Menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. - Hadi Wuryandanu; Zaenal Arifin (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
In the Indonesian government system, the DPD is a representation of the people, a state institution that is constitutionally given the authority and task of representing regional interests at the national level. The DPD not only proposes policies related to regional autonomy, but also ensures continued development and political stability in Indonesia. However, in practice, the DPD's role is limited by structural constraints and dependence on its partners, especially the DPR and the central government. The DPD relies heavily on the DPR to make decisions, which reduces its effectiveness. This limitation shows that the position of the DPD is not equal to that of the DPR. As a constitutional institution, it is important for the DPD to be given a more substantial role in policy making to ensure better representation for the regions. The main issue discussed is how the authority of the Regional Representative Council of the Republic of Indonesia (DPD-RI) is in strengthening regional autonomy and how DPD-RI as regional representatives can have equal rights and authority to the DPR-RI in fighting for regional interests. This research method uses a type of normative legal research that uses secondary data through literature searches. The conclusion drawn is that DPD-RI has limitations in supporting regional autonomy. Article 22D of the 1945 Constitution of the Republic of Indonesia as a result of the amendment actually weakens its position. The increase in authority is expected to strengthen its role as a balancer in the Indonesian political system.